Argumentation in chemistry teacher education: Past, present and future opportunities - Antonio Archila , Pablo (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article reports the results of a thesis about argumentation in Colombian chemistry teacher education. Firstly, literature review is discussed in order to determine how research advances in argumentation and science education are involved –or are not- into training Colombian chemistry teacher programs. Secondly, types of questions employed by three pre-service chemistry teachers are analyzed to understand how they provoke –or do not- students’ argumentation. Finally, the results of this study permit to suggest a program to educate future chemistry teacher based on how to enrich students’ learning through argumentation.